PENGARUH INTEGRITAS, OBJEKTIVITAS, KOMPETENSI TERHADAP KUALIATAS AUDIT PADA BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN PERWAKILAN PROVINSI SUMATERA UTARA - Lase, Jessica Renta Junita; OmpuSunggu, Patricia Esther Clara; Ginting, Wenny Anggresia (2021)
This analysis is intended to be able to understand the Integrity,Objectivity, and Competence, of Audit Qualityat the Financial Supersiviory Agency Development, Representative Office of North Sumatra. The approach used in this analysis is a qualitative approach. There are 60 samples that complete this analysis. This study uses multiple linear regression so the result is Objectivity and Competence was have a significant effect on Audit Quality at the Financial Supervisiory Agency Development, Representative Office of North Sumatra.